Synergy in the interaction of amoxicillin and methylene blue with dipalmitoyl phosphatidyl choline (DPPC) monolayers - Maximino, Mateus D. [UNESP]; Constantino, Carlos J.L. [UNESP]; Oliveira, Osvaldo N.; Alessio, Priscila [UNESP] (Elsevier, 2019)
Understanding molecular-level mechanisms in the action of emergent pollutants is essential to correlate with their possible impact on living organisms in the environment and on human health. In this study, we investigate the interactions between two widely used compounds classified as emerging pollutants and Langmuir monolayers of 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine (DPPC) that represent a simplified model of the lipidic structure of cell membranes. The pollutants studied were the antibiotic amoxicillin (AMX) and methylene blue (MB), a pharmaceutical drug also used as a dye in industry. AMX and MB were found to expand the surface pressure isotherms of DPPC, also affecting its morphology according to Brewster angle microscopy images. Significantly, when these compounds were mixed (MIX), monolayer expansion increased. The synergy in MIX activity was confirmed with in-situ polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) measurements, which indicated that electrostatic interaction with DPPC head groups was considerably stronger than for either AMX or MB. An adduct formed between AMX and MB in MIX also caused the DPPC monolayer thickness to increase, as inferred from measurements with grazing-incidence X-ray scattering out of the specular plane (GIXOS), in contrast to the decreased thickness induced by AMX or MB. That a mixture potentiates the interaction between contaminants and cell membrane models may be relevant for cocktail effects on living organisms.
Keywords: Amoxicillin; Emerging pollutants; Langmuir films; Membrane model; Methylene blue; Mixture of pollutants